2018
DOI: 10.9758/cpn.2018.16.1.376
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Treatment of Major Depressive Episodes with Mixed Features: A Systematic Review

Abstract: We reviewed clinical studies investigating the pharmacological treatment of major depressive episodes (MDEs) with mixed features diagnosed according to the dimensional criteria (more than two or three [hypo]manic symptoms+principle depressive symptoms). We systematically reviewed published randomized controlled trials on the pharmacological treatment of MDEs with mixed features associated with mood disorders, including major depressive disorder (MDD) and bipolar disorder (BD). We searched the PubMed, Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The KMAP‐BP has gradually come to view AAPs as primary drugs rather than just as adjunctive agents to MSs. AAPs are efficacious for difficult cases of depression, cases showing mixed features, and those with rapid cycling, as well as classical mania 4,5,35,38,39 . However, the preferred AAP differs depending on the KMAP‐BP edition and type of episode.…”
Section: Discussionmentioning
confidence: 99%
“…The KMAP‐BP has gradually come to view AAPs as primary drugs rather than just as adjunctive agents to MSs. AAPs are efficacious for difficult cases of depression, cases showing mixed features, and those with rapid cycling, as well as classical mania 4,5,35,38,39 . However, the preferred AAP differs depending on the KMAP‐BP edition and type of episode.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Moreover, recent studies have reported that major depressive episode (MDE) mixed features are characterized by a low prevalence, the predominance of anxious distress, the prevalence of cluster B personality disorders, and pharmacological treatment with antipsychotics. [25][26][27] Thus, as shown in Figure 1, the specifier "with mixed features" may indicate quantitative but not qualitative overlapping symptoms from one pole to the opposite pole in the dichotomization of mood disorders into bipolar and depressive disorders.…”
Section: Dichotomizing Mood Disorders Into Bipolar Disorders and Deprmentioning
confidence: 99%
“…See et al, 2021). This allows us to measure mixed depression and hypo/ mania symptoms, common to most BD mood episodes (Shim et al, 2018). Developing measures specifically for EMA is ideal; most researchers instead cherry-pick items from existing measures with limited pilot testing (i.e., psychometric properties untested ;Trull & Ebner-Priemer, 2020).…”
Section: Bd Symptom Measurementmentioning
confidence: 99%